(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: In recent past, the incident of lightning strikes and related injuries has increased significantly which is the detrimental consequence of climate change. Therefore, it is recognized as one of the cause of weather related death in Bangladesh. Objective: To present the pattern of lightning related injuries in Bangladesh. Materials and Methods: A cross sectional study carried out on September 2021 among 40 people who were victim of lightning on the way to attend a wedding reception in Shibganj upazila of Chapainawabganj on 4 August 2021. Detail information was received from one relative of each 16 deceased family and 24 survivors. Further, data were collected from the doctors and nurses of Chapainawabganj Government Hospital Results: In addition to the two fatalities on the route to the hospital, 14 individuals died on the spot. Further, among 24 survivors, 16 people survived with moderate and rest 8 survivors had mild injuries. 45% lightning victims were dead and 35% were survived with major injuries by lightning and 20% victims survived with minor injuries. Majority (35%) of death were due to direct strike which is followed by ground strike (30%). Injury to nervous and cardiovascular system is the usual site of injury for human organ where percentage of injury is 35% and 30% respectively. The victims remain admitted to hospital in varying range and survivors had multiple symptoms of minor injuries. Among them, majority victims (9 people) 40.91% left hospital after initial observation. Conclusion: Lightning kills few hundred and injures several thousand people in our country every year. However, lightning survivors should be taken to hospital for further investigation and treatment. Field management is very important for a patient to survive. For this, lightning education will immensely help not only to minimize the death cases but also help them to manage the lightning victims on the spot. JAFMC Bangladesh. Vol 19, No 1 (June) 2023:18-21